Chapter Plasmonics in Sensing: From Colorimetry to SERS Analytics - Kuttner, Christian (InTechOpen, 2018)
This chapter gives a brief overview of plasmonic nanoparticle (NP)-based sensing concepts ranging from classical spectral-shift colorimetry to the highly active field of surface-enhanced Raman scattering (SERS) spectroscopy. In the last two decades, colloidal approaches have developed significantly. This is seen with, for example, refractive-index sensing, detection of ad−/desorption and ligand-exchange processes, as well as ultrasensitive chemical sensing utilizing well-defined nanocrystals or discrete self-assembled superstructures in 2D and 3D. Apart from individual NPs, the rational design of self-assembled nanostructures grants spectroscopic access to unprecedented physicochemical information. This involves selected research examples on molecular trapping, ligand corona analysis, SERS-encoding, and biosensing. The origin of the SERS effect, also in regard to hot spot formation by off-resonant excitation, is reviewed and discussed in the context of the current challenge to formulate a generalized metric for high SERS efficiency. Special emphasis lies in addressing the fundamental design criteria and the specific challenges of these particle-based sensing techniques.